Basic life support training for laypeople in West Martapura District, South Kalimantan - Ida Yuliana; Fauzan Muttaqien; Fahrina Ulfah; Irfan Maulana (Community Empowerment, 2023)
Proficiency in basic life support (BLS) techniques significantly increases the chances of survival for victims, boosting their likelihood of recovery by approximately 80%. Basic life support involves actions aimed at maintaining an open airway, assisting with breathing, and ensuring circulation without the need for specialized equipment. These skills can be acquired by the general public without requiring extensive medical education. As a result, the primary objective of this community service initiative is to enhance the knowledge and proficiency of basic life support (BLS) among laypeople in the West Martapura District. Our methods include lectures, question-and-answer sessions, practical demonstrations, focus group discussions (FGDs), and hands-on BLS training using mannequins, all under the guidance and supervision of qualified instructors. The outcome of this program is an improved understanding and competency in applying BLS techniques, empowering ordinary individuals to confidently assist those in need within their community.